2001
DOI: 10.1046/j.1365-2249.2001.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

FTS reduces bleomycin-induced cytokine and chemokine production and inhibits pulmonary fibrosis in mice

Abstract: SUMMARYBleomycin (BLM), an antitumour drug, is known to cause interstitial pneumonia followed by pulmonary fibrosis, and has often been used to produce an animal model of pulmonary fibrosis. In the present study, we examined the effect of a nonapeptide thymic hormone, facteur thymique serique (FTS), on the murine lung fibrosis induced by intratracheal instillation of BLM. Treatment with FTS ameliorated BLM-induced fibrotic changes in a dose-dependent manner, as indicated by the reduced accumulation of hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…TNF-α functions as a chemokine in inflammatory cells, in addition to promoting the synthesis of fibronectin, prostaglandin and TGF-β. Depletion of TNF-α by antibodies has demonstrated a beneficial effect in the inhibition of bleomycin-induced lung injury (28,29). In the present study, a marked increase in TNF-α levels in the lungs occurred following bleomycin exposure, which was suppressed by apigenin treatment in a dose-dependent manner (Fig.…”
Section: A B a B Csupporting
confidence: 62%
“…TNF-α functions as a chemokine in inflammatory cells, in addition to promoting the synthesis of fibronectin, prostaglandin and TGF-β. Depletion of TNF-α by antibodies has demonstrated a beneficial effect in the inhibition of bleomycin-induced lung injury (28,29). In the present study, a marked increase in TNF-α levels in the lungs occurred following bleomycin exposure, which was suppressed by apigenin treatment in a dose-dependent manner (Fig.…”
Section: A B a B Csupporting
confidence: 62%
“…Facteur thymique serique early (Yara et al, 2001) 19 5 rhIL-1 beta early (M. Yasui et al, 1991) 19 6 APC early (H. Yasui et al, 2001) 19 7 CD36 early (Yehualaeshet et al, 2000) 19 8 KGF early (Yi et al, 1996) 19 9…”
Section: Idmentioning
confidence: 99%
“…Researchers have reported that several drugs, including macrolide compounds, 24) thymic hormone, 25) and herbal compounds, 26) have anti-fibrotic actions in the experimental animal models of pulmonary fibrosis. The mechanisms underlying the anti-fibrotic actions of these drugs on lung fibroblasts are yet to be determined.…”
Section: Resultsmentioning
confidence: 99%